Optimalisasi Pemanfaatan Ecoenzym dalam Budidaya Hortikultura Urban Farming untuk Mendukung Ketahanan Pangan Keluarga pada KWT Kota Pala Desa Dauh Peken Tabanan - L P K Pratiwi; I N Ariana Guna; Ananda Wiguna; I M Ananda Wiguna; I M A Wahyu Utami; N L Sintya Dewi; M D Pasaribu; A U Galih Cahayaningsih (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
Abstract. The Women Farmers Group (KWT) Kota Pala in Dauh Peken Village, Tabanan Regency, has developed urban farming activities and produces eco-enzyme from household organic waste. However, its application in horticultural cultivation remains limited due to insufficient knowledge and technical skills regarding proper dosage, application methods, and benefits for plant growth. This community service program aimed to improve members’ capacity to utilize eco-enzyme as a liquid organic fertilizer for sustainable horticultural cultivation. Conducted in May 2026, the program involved 20 KWT members through educational sessions, hands-on training, field demonstrations, mentoring, and evaluation. Eco-enzyme was applied to pak choi, mustard greens, and lettuce as demonstration crops. Program effectiveness was evaluated using pre-test and post-test scores, participants’ practical skills, and their level of participation. The results showed that participants’ knowledge increased from 52.50% to 88.00%, while practical application skills improved from 41.30% to 86.50%. Sixty horticultural plants were used as demonstration plots, achieving a 90.00% technology adoption rate. The program effectively strengthened participants’ knowledge and skills, promoting sustainable urban farming practices and supporting household food security through the use of locally available resources